SOIL ORGANIC CARBON AND PHOSPHORUS STATUS AFTER COMBINED APPLICATION OF PHOSPHATE ROCK AND ORGANIC MATERIALS IN A GYPSIFEROUS SOIL* - & Al-kafaje, Muhawish (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Gypsiferous soils in Iraq are suffering from low fertility due to low levels of organic matter and limited availability of nutrients especially phosphorus (P). Therefore, two experiments were conducted to study the impact of combination of low cost phosphate rock (PR) and organic materials (OM) on soil organic carbon (SOC) and P status. The first experiment was an incubation experiment which was conducted to determine level of organic carbon (OC) required for the second experiment, this experiment was consisted of two factors the first was level of OC (as sheep manure) applied at nine levels viz: 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, and 0.60% of soil weight, the second factor was level of PR (0, 20, 40, and 60 mg P kg-1 soil). The second experiment was a greenhouse pot experiment with two factors, the first was P source [Triple Super Phosphate (TSP), PR, PR+ Peat, and PR+ Manure), the second factor was P level (0, 30, 60, and 90 mg P kg-1 soil). Wheat (Triticum aestivum) was grown in the second experiment. Results from incubation experiment showed that increasing OC application increased available P (Avail. P) and Water Soluble P (WSP) as expressed by power and exponential models, respectively. Available P was also increased linearly by increasing P level in soil (incubation experiment). Results of pot experiment revealed that the fourth treatment (PR+manure) was significantly superior over other treatments in increasing root weight, organic P (OP), and Avail. P, while the third treatment (PR+Peat) was significantly superior over other treatments in increasing SOC.